1987
DOI: 10.1038/326507a0
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of c-"os gene transcription by negative and positive cellular factors

Abstract: Regulation of transcription in eukaryotes is mediated by the specific interaction between cellular factors and promoter sequences. Cis-acting DNA sequences, frequently located upstream of the TATA box, have been implicated in modulating the expression of many genes. We are interested in the transcriptional regulation of proto-oncogenes because they may have a pivotal function in cell growth and differentiation. Expression of the proto-oncogene c-fos is induced in response to a variety of growth factors and dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(46 citation statements)
references
References 26 publications
1
45
0
Order By: Relevance
“…We have demonstrated that in asynchronously growing HeLa cells, induction of c-fos by both EGF Recent observations from in vivo competition experiments with transfected genes suggest that c-fos expression may be regulated by negatively acting factors as well as requiring a positive factor(s) (37). We have not found any evidence for a negatively acting factor from our mutational analysis; however, we would not have detected one if such a factor bound to the enhancer region and if our point mutations in the enhancer abolished binding of both the negatively and positively acting factors.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that in asynchronously growing HeLa cells, induction of c-fos by both EGF Recent observations from in vivo competition experiments with transfected genes suggest that c-fos expression may be regulated by negatively acting factors as well as requiring a positive factor(s) (37). We have not found any evidence for a negatively acting factor from our mutational analysis; however, we would not have detected one if such a factor bound to the enhancer region and if our point mutations in the enhancer abolished binding of both the negatively and positively acting factors.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the c-fos oncogene group interacts with many stimulants and plays a role in cell growth and development (26). Generally, increased expressions of FOS in malignant tumors were also observed in fibroblasts when they were in stress.…”
Section: Discussionmentioning
confidence: 81%
“…Many examples of mammalian transcription units that contain cis-acting negative regulatory elements are now well documented. In particular, most of these genes are susceptible to induction by hormonal or environmental influences (12,31) or show very restricted patterns of tissue expression (17,25 genes. This mechanism would ensure that genes remain transcriptionally silent in the absence of the proper cellular signals or in inappropriate cell types.…”
Section: Discussionmentioning
confidence: 99%
“…interferon gene (12) and the c-fos gene (31), contain negative cis-acting transcriptional elements. Additionally, some cellular genes whose expression is regulated in a tissue-specific manner-for example, the rat insulin gene (25) and the immunoglobulin heavy-chain gene (17)-also contain cisacting negative elements.…”
mentioning
confidence: 99%